2022
DOI: 10.1590/fst.51120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rhizosphere inoculation with Bacillus strains and phytopathogens on the contents of volatiles and human health-related compounds in tomato fruits

Abstract: This study consisted of determining the effect of Bacillus strains inoculated alone or in combination with phytopathogenic fungi on the production of human health-related compounds and volatile organic compounds (VOCs) in tomato fruits. Seedlings were cultivated under greenhouse conditions and inoculated with B. amyloliquefaciens, B. methylotrophicus and B. subtilis alone or in combination with Alternaria solani, Fusarium oxysporum and Phytophthora infestans. Fully ripe fruits were harvested and evaluated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…The authors attributed the increase in phenylalanine-derived volatiles to the up-regulation of the phenylpropanoid pathway, producing, in turn, an array of antioxidant compounds modulating the plant's response to root colonization by the AM fungi. Such an interpretation seems coherent with the results of Ruiz-Cisneros et al [96] who subjected the greenhouse tomato 'Merlice' to a root application of Bacillus amyloliquefaciens, B. methylotrophicus and B. subtilis, alone or in combination. The authors reported a PGPR-derived increase in fruit concentration of volatiles having a role as antimicrobials (2-hexenal) or in systemic acquired resistance by the plant (methyl salicylate), together with enhanced concentrations of carotenoids, phenolic acids and associated volatiles.…”
Section: Plant-beneficial Microorganismssupporting
confidence: 87%
“…The authors attributed the increase in phenylalanine-derived volatiles to the up-regulation of the phenylpropanoid pathway, producing, in turn, an array of antioxidant compounds modulating the plant's response to root colonization by the AM fungi. Such an interpretation seems coherent with the results of Ruiz-Cisneros et al [96] who subjected the greenhouse tomato 'Merlice' to a root application of Bacillus amyloliquefaciens, B. methylotrophicus and B. subtilis, alone or in combination. The authors reported a PGPR-derived increase in fruit concentration of volatiles having a role as antimicrobials (2-hexenal) or in systemic acquired resistance by the plant (methyl salicylate), together with enhanced concentrations of carotenoids, phenolic acids and associated volatiles.…”
Section: Plant-beneficial Microorganismssupporting
confidence: 87%
“…Regarding tomato biofertilization, Ochoa-Velasco et al [ 18 ] reported that the application of the strain B. licheniformis at 75% of the full N dose increased the antioxidant capacity of the fruits for the DPPH (1.9×) and the FRAP (1.4×) assays with respect to the non-inoculated treatment. Similarly, Ruiz-Cisneros et al [ 52 ] reported an increase in the content of phenols (1.5×) and antioxidant activity (2.8×) in tomato fruits biofertilized with Bacillus spp. strains in comparison with the control without inoculation.…”
Section: Discussionmentioning
confidence: 84%
“…Cherry tomato is popular because of its rich nutrition and juicy taste. However, the postharvest life of this fruit is relatively short, which is limited by postharvest water loss, disease, ripening and aging (Ruiz-Cisneros et al, 2022;Panjai et al, 2017), reducing the acceptance and quality of fruit after storage. Botrytis cinerea is the most common microbial infectious disease of cherry tomato (Wang et al, 2010).…”
Section: Effect Of Thymol On Physical Properties Antimicrobial Proper...mentioning
confidence: 99%